Analysis of the Deforestation Process of Amazon from During 2001 to 2020 in Peru - Chulluncuy Samaniego, Anali (2023)
Latin America suffers from a major problem of loss of Amazonian Forest cover, thus making Peru one of the ten most diverse countries on the planet where most of our biological diversity is found in forests and these provide us with various ecosystem services and play a very important in nature. To calculate forest loss, the database of the "Geoforests" platform of the PNCBMCC (National Forest Conservation Program for Climate Change Mitigation) of the Ministry of the Environment was obtained, where Landsat-TM, Landsat- ETM+ and Landsat-OLI during the periods 2001-2020. Based on the evidence, it is concluded that the Peruvian Amazon Forest, over the years, has increased hectares of loss and fragmentation of dangerous forests, predicting that by 2030 there will be almost 4 million hectares lost according to the average of annual growth, being the main causes of agriculture, illegal mining and opening of roads, prevailing the negative aspects such as the loss of biodiversity contributing to climate change.